Personal Agency Enhancing Model in Prevention of Diabetic Foot Ulcer - Nasrun Pakaya; K Kusnanto; Hari Basuki Notobroto; Rika Subarniati Triyoga (Universitas Aisyah Pringsewu, 2021)
Diabetes mellitus (DM) is an increase in blood sugar levels which can cause complications.. Uncontrolled diabetes can cause various complain in patients. Objective: Analyzing the characteristics of respondents with psychosocial, the characteristics of respondents with the personal agency, and psychosocial with the personal agency for the prevention of diabetic foot ulcer. Method: The design used was a cross-sectional study with simple random sampling using psychosocial instruments and the personal agency for diabetic foot ulcer prevention with a total of 329 respondents from the age of 30 to 75. The data were analyzed using SEM-PLS software. Results: 221 patients had no history of diabetes, and most of them had good knowledge, 4 respondents experienced severe stress, mostly with high perceived control (52.3%), low self-efficacy (53.2%), and low personal agency (51.1%).There is no relationship between the characteristics of the respondent and the personal agency.There is no relationshipbetween the psychosocial with the personal agency.There is a relationship between psychosocial with the personal agency for preventing diabetic foot ulcer. Conclusion: The variables of knowledge and stress have a large direct contribution to the improvement of the personal agency for diabetic foot ulcer prevention.